2018
DOI: 10.1111/coa.13245
|View full text |Cite
|
Sign up to set email alerts
|

Single‐sided deafness and cochlear implantation in congenital and acquired hearing loss in children

Abstract: Objective:To determine the audiological and clinical results of cochlear implantation in children below the age of 12 years old with congenital and acquired singlesided deafness.Design: Observational, descriptive, transversal study. Main outcome measures: Speech reception thresholds, Cortical responses, AuditoryLateralization Test and SSQ questionnaire.Participants: Children < 12 implanted for congenital or acquired SSD.Results: All the children with congenital SSD showed positive cortical responses.Positive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 26 publications
1
63
0
3
Order By: Relevance
“…1,4,6,18 Similarly, some children with single-sided deafness have obtained significant audiological and subjective benefits from cochlear implantation. 4,5,19 Unlike the contralateral routing of signal and BAHA devices, cochlear implantation helps patients with single-sided deafness obtain bilateral input and restores bilateral hearing, rather than simply transmitting sound signals to the normal ear. 1,4 However, patients with single-sided deafness who received cochlear implantation experienced different stimulation of their ears when electrical and acoustic stimulations arose from their impaired ear and normal-hearing ear separately.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,6,18 Similarly, some children with single-sided deafness have obtained significant audiological and subjective benefits from cochlear implantation. 4,5,19 Unlike the contralateral routing of signal and BAHA devices, cochlear implantation helps patients with single-sided deafness obtain bilateral input and restores bilateral hearing, rather than simply transmitting sound signals to the normal ear. 1,4 However, patients with single-sided deafness who received cochlear implantation experienced different stimulation of their ears when electrical and acoustic stimulations arose from their impaired ear and normal-hearing ear separately.…”
Section: Introductionmentioning
confidence: 99%
“…CI in children with congenital SSD provides some benefits of binaural hearing if implantation occurs within the critical period of auditory development. 4,19,21 The ideal implantation window in children with congenital SSD might be short, as expected, and may be at an age younger than 4 years. 18,19,21 Rehabilitation training of patients with congenital SSD with CI UAD leads to asymmetrical changes in the sound localization pathway.…”
Section: Age Of CI In Children With Congenital Ssdmentioning
confidence: 78%
“…To date, the precise end of the possible CI window is unknown. Based on most previous results, 4,18,19,21 we consider that the results by Thomas et al 17 may be too optimistic. These authors found that there was no difference in results between an implantation age of >6 years and <6 years, 17 which is debatable.…”
Section: Age Of CI In Children With Congenital Ssdmentioning
confidence: 92%
See 1 more Smart Citation
“…Cochlear implantation (CI) for single-sided deafness was firstly considered as a treatment to suppress severe tinnitus in adults, and, shortly after, binaural hearing re-establishment was considered as another benefit of this implantation on the singlesided hearing loss (3)(4)(5). CI as a beneficial treatment for adults suffering from acquired SSD is well-established in a growing number of countries, but there is little experience about this treatment option in children (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%